Oral recombinant Mycobacterium bovis bacillus Calmette-Guérin expressing HIV-1 antigens as a freeze-dried vaccine induces long-term, HIV-specific mucosal and systemic immunity - Kawahara, Mamoru (Clinical immunology (Orlando, Fla.), 2002)
Induction of HIV-1-specific immune responses was evaluated using a recombinant BCG (rBCG) vector-based vaccine expressing HIV-1 Env V3 peptide (rBCG-pSOV3J1). rBCG-pSOV3J1 was manufactured as a freeze-dried preparation based on good laboratory practice guidelines. Guinea pigs were immunized with the freeze-dried rBCG vaccine by oral administration to test the effectiveness of what is generally considered the most convenient and practical route for vaccination. While delayed-type hypersensitivity (DTH) skin reactions to purified protein derivative were not detected in any of the animals receiving oral rBCG-pSOV3J1, HIV-1 V3J1 antigen-specific DTH responses were detected in all of the immunized guinea pigs 1.5 years after immunization. In addition, significant proliferative responses against HIV-1 V3J1 antigen were measured in peripheral blood mononuclear cells and splenocytes from all animals receiving oral rBCG. Interestingly, intestinal intraepithelial lymphocytes from the animals also exhibited high levels of proliferative activity against HIV-1 V3J1 antigen. These results suggest that oral vaccination of guinea pigs with freeze-dried rBCG-pSOV3J1 induces high levels of functional T cells specific for HIV-1 antigens in both mucosal and systemic compartments and suggest that this approach has potential for use as a vaccine against HIV-1